Explicit Determinant and Inverse Formulas of Skew Circulant Matrices with Alternating Fibonacci Numbers - Sapto Mukti Handoyo; Sugi Guritman; Teduh Wulandari Mas'oed; Jaharuddin Jaharuddin (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
Skew circulant matrices have various applications such as cryptography, signal processing, and many more. Their structure can potentially simplify their determinant and inverse computations. This study presents explicit formulas for the determinant and inverse of skew circulant matrices with entries from the alternating Fibonacci sequence. Elementary row and column operations are used to derive simple explicit formulas for the determinant and inverse. Computational tests using Wolfram Mathematica show that the algorithm built from these explicit formulas performs with much faster execution time than the built-in functions, especially for large matrix size. The proposed approach offers a practical method for the numerical computation of the determinant and inverse of these matrices